Lowland Tropical Peatlands – A Brief Review of Their Important Role in the Global Carbon Cycle and Biodiversity Support - Page, Susan E (Media Konservasi, 2024)
Tropical peatlands are crucial ecosystems, storing vast carbon reserves and supporting rich biodiversity. Despite covering a small land area, they play significant roles in global carbon cycling and climate regulation. However, these ecosystems face escalating threats from human activities, including agricultural expansion and peatland drainage. This paper provides a concise overview of tropical peatlands, focusing on their distribution, characteristics, and ecological importance in Southeast Asia, Africa, and South America. It highlights the diverse vegetation communities and notable animal species found in peat swamp forests, underscoring their conservation value. Peatland degradation leads to increased greenhouse gas emissions, land subsidence, and loss of traditional livelihoods for local communities. Addressing these challenges requires integrated approaches, including conservation efforts to protect and restore intact peat swamp forests, sustainable land-use practices, and policy interventions to regulate land management. Research collaboration between scientists, policymakers, and local communities is essential for developing evidence-based conservation strategies. By prioritizing the preservation of tropical peatlands, we can mitigate climate change impacts, conserve biodiversity, and safeguard the well-being of local communities.